Appreciative inquiry: an alternative re- search approach for sustainable rural tourism development / Roslizawati Che Aziz ... [et al.] - Che Aziz, Roslizawati; Abdul, Mohani; Abdul Aziz, Yuhanis; Abd Rahman, Azmawani (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA (UiTM), Malaysia, 2013)
Tourism is one of the world's fastest growing industries, and is a major source of income for developing countries. The opportunities offered by the tourism industry globally are unquestionable, and every country seeks to stimulate sustainable economic growth based on employment opportunities. Study on the potential of developing tourism activities in rural areas may increase benefits received from tourism activities that will ensure synergy between tourism development and biodiversity conservation. Thus, this paper attempts to discuss the significance of sustainable rural tourism development and the application of Appreciative Inquiry approach as one of the alternative tourism research tool. AI may offer researchers another worldwide and methodology for framing and conducting tourism re- search. It does not mean that AI will replace all research approaches or can overcome all the challenges of conducting research. However, AI can be considered as a new method, approach or strategy for tourism research, which initiates positive changes especially in rural communities.